A Supervoid Explanation of the Cosmic Microwave Background Cold Spot. Issue Volume 10:Issue S306(2014) (1st July 2015) - Finelli, F.; García-Bellido, J.; Kovács, A.; Paci, F.; Szapudi, I.
Abstract: The Cold Spot is an anomalously cold region in the Cosmic Microwave Background (Vielva et al .2004 ), either caused by a structure in the line of sight or could be of primordial origin. We search for a supervoid aligned with the Cold Spot region, filling the gap in redshift at z <0.3 which has never been explored in details. We find a large projected under density in the recently constructed WISE-2MASS catalogue, whose median redshift is z ≃ 0.14, with an angular size of 30 degrees. We show that a spherically symmetric Lemaitre-Tolman-Bondi (LTB) void model can simultaneously fit the δ gal / b =δ 2D ≃ −0.12 underdensity in the WISE-2MASS catalogue, and the Cold Spot as observed by both the WMAP and Planck satellites. Such an LTB supervoid gives a plausible explanation of the Cold Spot anomaly, and is preferred over the null hypothesis or a texture model.